Security analysis of TORA routing protocol - Chee, Vee Liem; Yau, Wei Chuen (2007)
In this paper, we present security analysis on Temporally-Ordered Routing Algorithm (TORA) routing protocol. We first identify three attack goals, namely route disruption, route invasion and resource consumption. Then, we study on how to achieve these attack goals through misuses of routing messages. The analysis shows that three misuse actions on the routing messages, including drop, modify and forward, and active forge, enable the malicious attacker to conduct real time attacks on TORA protocol. We demonstrate the attacks using NS-2 software and then analyze the simulation results. The simulation results verify our analysis and we observe that through certain misuses, an inside attacker can degrade the network performance, disrupting the route creation process and consume scarce network resource.